Poster Presentations 2019
DOI: 10.1136/annrheumdis-2019-eular.7860
|View full text |Cite
|
Sign up to set email alerts
|

Thu0072 ultrasound Predicts Imminent Progression to Arthritis in Anti-CCP Positive at-Risk Individuals

Abstract: BackgroundUltrasound (US) Power Doppler (PD) signal is predictive for the development of inflammatory arthritis (IA) in anti-cyclic citrullinated protein antibodies positive (CCP+) individuals with musculoskeletal (MSK) symptoms but no clinical synovitis (CS) [1]. Our previous data showed a late increase in the overall US inflammation before arthritis development, suggesting that a sub-clinical phase of synovitis could be detected [2]. This abstract describes the prediction of PD abnormalities in the months fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“… 77 92 In those with symptoms, the development of US synovitis appears to be a relatively late event, reflecting imminent clinical arthritis, 93 especially as more joints become involved. 94 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 77 92 In those with symptoms, the development of US synovitis appears to be a relatively late event, reflecting imminent clinical arthritis, 93 especially as more joints become involved. 94 …”
Section: Resultsmentioning
confidence: 99%
“…77 92 In those with symptoms, the development of US synovitis appears to be a relatively late event, reflecting imminent clinical arthritis, 93 especially as more joints become involved. 94 MRI studies in ACPA+ individuals with MSK symptoms and patients with CSA have identified tenosynovitis as both the most prevalent abnormality and the strongest MRI risk factor for arthritis development. 35 50 95 Tenosynovitis was the only MRI abnormality associated with arthritis progression at patient level in a study of 98 ACPA+ individuals with MSK symptoms (HR 4.02 (1.91-8.44), p=0.002).…”
Section: At-risk Individuals With Msk Symptoms But Without Clinical Arthritismentioning
confidence: 99%
“…Moreover, some might argue that US ‘sub-clinical’ inflammation might represent a late stage in the RA ‘continuum’, and when present may represent an irreversible progression to IA. Indeed, recent data suggest that the presence of PD in more the three joints, in anti-CCP ‘at-risk’ individuals, is virtually synonymous with imminent progression to RA [ 35 ]. In the context of clinical trials for disease prevention, this poses the question whether ‘at-risk’ individuals should be approached for these trials before the development of ‘sub-clinical’ synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…34 In a subsequent analysis of 307 subjects, the frequency of US PD at patient level (ie, number of joints affected) increased in the 12 months prior to arthritis development. 35 In a Dutch seropositive arthralgia cohort, US changes (ie, PD signal, GS synovitis, erosions) were associated with arthritis development at joint level but not patient level, although the US protocol contained fewer joints compared with the UK cohort studies. 36 In a subsequent study, GS synovitis (grade ≥2) was associated with the development of arthritis and its timing at patient level (metatarsophalangeal (MTP) joints excluded); HR 3.4.…”
Section: Clinical Featuresmentioning
confidence: 96%